معوِّقات استخدام أسلوب البرمجة الخطية في عمليَّة اتِّخاذ القرارات الإداريَّة "دراسة ميدانيَّة على الشَّركات الصِّناعيَّة العاملة في السَّاحل السُّوري" (Latakia University Journal - Economic and Legal Sciences Series, 2018)
جاء هذا البحث للوقوف على مدى تأثير معوِّقات استخدام أسلوب البرمجة الخطية (المعوِّقات المتعلِّقة بمتَّخذ القرار، المعوِّقات المتعلِّقة بأسلوب البرمجة الخطية ذاته، المعوِّقات المتعلِّقة بالمؤسَّسة، والمعوِّقات المتعلِّقة بالبيئة الخارجيَّة) على استخدام هذا الأسلوب في عمليَّة اتِّخاذ القرارات الإداريَّة، وذلك في عيِّنة من الشَّركات الصِّناعيَّة العاملة في السَّاحل السُّوري. قام الباحث بتوزيع (90) استبياناً على المديرين ورؤساء الأقسام والمراقبين وأفراد الكوادر الإداريَّة المسؤولة عن اتِّخاذ أشكال وأنواع مختلفة من القرارات الإدارية في الشَّركات محل الدراسة ، وقد بلغ عدد الاستبانات المستردَّة والصَّالحة للتَّحليل والَّتي تمَّ تفريغها (75) استبانة. قام الباحث بتحليل البيانات باستخدام برنامج التَّحليل الإحصائي (SPSS 20). وفي نهاية هذا البحث توصَّل الباحث إلى مجموعة من الاستنتاجات وأهمّها: يوجد تأثير معنوي لجميع المعوِّقات المدروسة (المعوِّقات المتعلِّقة بمتَّخذ القرار، المعوِّقات المتعلِّقة بأسلوب البرمجة الخطية ذاته، المعوِّقات المتعلِّقة بالمؤسَّسة، والمعوِّقات المتعلِّقة بالبيئة الخارجيَّة) على استخدام الإدارة لأسلوب البرمجة الخطية في الشَّركات محل الدراسة. كما تقدَّم الباحث في نهاية البحث بمجموعة من التَّوصيات والَّتي كان أهمُّها: الاهتمام بتدريب المدراء ومتَّخذي القرارات والعاملين في الشَّركات محل الدراسة على استخدام أسلوب البرمجة الخطية وزيادة معارفهم به وبمجالات استخدام الحاسوب والبرامج ذات العلاقة من خلال الدَّورات التَّدريبيَّة وورش العمل بطرق حديثة تحاكي النَّمط الواقعي للمساهمة في بناء نظم فعَّالة توافق بيئة العمل، وضرورة المواكبة المستمرة للمستجدَّات التِّقنيَّة في مجال هذا الأسلوب.   This research was conducted to determine the extent to which the constraints of the use of the linear programming method (constraints related to the decision maker, the constraints related to the linear programming method itself, constraints related to the institution, and constraints related to external environment) affect the use of this method in the decision making process in a sample of industrial companies Operating in the Syrian coast. The researcher distributed (90) questionnaires to managers, heads of departments, supervisors and administrative personnel responsible for taking various forms and types of administrative decisions in the companies in question. The number of recovered and valid questionnaires which were discharged was (75). The researcher analyzed the data using the Statistical Analysis Program (SPSS 20). At the end of this research, the researcher reached a number of conclusions, the most important of which is: There is a significant effect on all the studied obstacles (constraints related to the decision maker, constraints related to the linear programming method itself, constraints related to the institution and external environment constraints). At the end of the research, the researcher presented a set of recommendations, the most important of which were: Attention to the training of managers, decision makers and employees in the companies under study on the use of the linear programming method and increasing their knowledge of it and the use of computers and related programs through training courses and workshops in modern ways. Building effective systems that are compatible with the work environment, and the need to keep abreast of technical developments in this field.